Anti-social and criminal conduct: its relationship with identity with socionormative peers (Research, Society and Development, 2020)
The antisocial behaviors comprehend inobservant behaviors as leaving without permission or profanities (antisocial) as those that directly infringe the penal code, such as stealing things, carry a weapon (criminal behaviors). Regarding the explanation of this construct, there is a consensus among researchers who say that this is an issue that involves several factors for its manifestation. Have pairs partner-normative, they refer to groups that are the basis for socialization of the individual, ie father, mother and teacher. Thus, the present study aims to verify the pattern of relationship between identity with socio-normative peers and antisocial and criminal behaviors.The participants were 188 youth and adults from the city of Parnaíba, Piauí, both sexes, of which 100 (53.2%) were women and 88 (46.8%), with a mean age of 22.25 years (SD = 3.04; range from 16 to 40), the majority declared unmarried (95%) and be enrolled in higher education (93%) and 64% belong to the middle class. The participants answered two instruments: an antisocial and criminal behaviors Questionnaire in its reduced version of the 20 items, the Social-Normative Peers Identification Scale and an Sociodemographic questions. The results indicated that the identification with socialnormative peers was inversely related to antisocial behaviors, however not correlated with criminal behavior. Moreover, it confirmed the hypothesis that women are less likely to have socially deviant behavior related to men. It is important to emphasize that one of the limiting aspects of this study was the type of sample used (for convenience), which is far from the reality of authors who research on the construct of criminal behavior. Finally, these results confirm previously published studies and it is concluded, however, there is still a long way to explore, especially regarded to the development of strategies to help the identification with social-normative as a protective factor for antisocial and criminal behaviors.